2007
DOI: 10.1177/039463200702000415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coronary Percutaneous Revascularization on Interferon-γ and Interleukin-10 Producing CD4+ T Cells during Acute Myocardial Infarction

Abstract: T lymphocytes play an important role in the induction and progression of acute coronary syndromes (ACS). To gain insight into how different T cell subsets can influence ACS, we analyzed the frequencies of circulating CD4+T cells producing either pro-inflammatory interferon(IFN)-y or anti-inflammatory interleukin (IL)-tO in subjects presenting with ST-elevation myocardial infarction (STEMI). The effect of coronary bare metal (BS) and paclitaxel-eluting stent (PES) on the balance between CD4+IFN-yand CD4+IL-tO+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The noted rise in IL-10 level could be due to the increased activation of proinflammatory interleukins that promotes the secretion of antiinflammatory IL-10 (23). The present study is in line with previous reports which showed an increase in IL-10 level in STEMI patients (24). In one study, Karpi nski et al (2008) reported the significant rise in IL-10 level in the acute phase of myocardial infarction (25).…”
Section: Discussionsupporting
confidence: 91%
“…The noted rise in IL-10 level could be due to the increased activation of proinflammatory interleukins that promotes the secretion of antiinflammatory IL-10 (23). The present study is in line with previous reports which showed an increase in IL-10 level in STEMI patients (24). In one study, Karpi nski et al (2008) reported the significant rise in IL-10 level in the acute phase of myocardial infarction (25).…”
Section: Discussionsupporting
confidence: 91%
“…In the cardiovascular system this receptor is present on both adherent cardiovascular system cells and on circulating inflammatory cells (39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) . It is involved in balancing degradation processes initiated by inflammatory cells and in the response of adherent cells to alterations in surrounding extra cellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory compounds are targeted for therapeutic intervention because of their role in promoting or sustaining harmful inflammation (Hansson 2005;Inoue et al 2008;Sardella et al 2007;Lavagno et al 2007;Bruzzese 2008). Substance P (SP) is an undecapeptide belonging to a group of proteins named tachykinins and is the key transmitter of pain to the brain (García-Horsman et al 2007;Katsanos et al 2008a;Katsanos et al 2008b).…”
Section: Introductionmentioning
confidence: 99%